Managing Diversity in Public Sector Workforces - Riccucci, Norma (New York, NY : Routledge, 2021)
"Today, public and private sector workforces in the U.S. look very different than they did even 25 years ago. The changes are having a significant effect on how organizations manage their workforces. The old styles of managing heterogeneous workforces are proving to be ineffectual, and so management strategies aimed at embracing diversity and inclusion are essential. These strategies can have positive implications for worker satisfaction, morale and -- ultimately -- the delivery of public services to the American people. Managing Diversity in Public Sector Workforces, Second Edition examines demographic changes to the U.S. labor force and workplace and the ways in which government employers are managing the diverse populations that now fill public sector jobs. Addressing specific management strategies and initiatives relied on by public sector employers, as well as the implications of effectively managing variegated workforces for the overall governance of American society, this book demonstrates the importance of ensuring that programs to promote inclusiveness and diversity that appear on paper are carried through to practice through implementation. The book begins with a review of equal employment opportunity and affirmative action and the extent to which EEO and AA are still relied upon in the workplace. It then examines law and other public policy issues surrounding EEO, AA and diversity management. The remainder of the book focuses on the core of managing diversity in the public sector, exploring the initiatives, strategies, and programs that government employers either do or might rely on to ensure that the demographic mosaic embodied by their workforces is prepared to meet the needs and interests of the American citizenry of the twenty-first century. Data are provided on the demographics of the federal, state and local government workforces. Separate chapters address each of the following aspects of diversity: race, ethnicity, gender, LGBTQ employment, physical ability, and the intersection of these constructs. Managing Diversity in Public Sector Workforces, Second Edition will be of interest to students of public administration and public personnel management, and it is essential reading for all those involved in managing public organizations"--
Introduction: Workforce Diversity and the Twenty-First Century -- Law and Public Policy: EEO, Affirmative Action and Diversity Management -- The Significance of Diversity and Social Equity -- Race and Diversity Management -- Managing Diversity around Ethnicity -- Diversity Management and Women in Public Sector Workforces -- Diversity and LGBTQIA -- Disability and Diversity in the Workplace -- Diversity, Diversity Management and Intersectionality -- Public Sector Organizations Positioning for the Future.
OCLC-licensed vendor bibliographic record.
Keywords: Civil service -- United States -- Personnel management; Diversity in the workplace -- United States; POLITICAL SCIENCE / Public Affairs & Administration